On the taxonomy of Ptychognathus andamanicus Alcock, 1900 (Crustacea: Decapoda: Brachyura: Varunidae) from the Andaman Islands, India - Patel, Heris; Mendoza, Jose C. E.; Bineesh, K. K.; Mitra, Santanu; Trivedi, Jigneshkumar N. (Zootaxa, 2025)
The identity of “Ptychognathus andamanica Alcock, 1900” originally described from Saddle Hill in North Andaman Island, India, is clarified. This species was synonymized with Ptychognathus riedelii (A. Milne-Edwards, 1868) based on the morphological characters of female specimens described by Alcock, 1900. A re-examination of the sole remaining syntype female (deposited in the Zoological Survey of India collection and herein designated as the lectotype) and a fresh male specimen collected from the Andaman Islands revealed that P. andamanicus is morphologically distinct from P. riedelii. Hence, P. andamanicus is herewith considered as a valid species. Ptychognathus andamanicus is redescribed and illustrated in the present study and its morphological differences with P. riedelii are discussed in detail.